A comparative study of porcine antihuman lymphocyte globulin versus antithymocyte globulin-fresenius in an allogeneic hematopoietic cell transplantation conditioning regimen for severe aplastic anemia. Issue 1 (1st January 2021) - Zhang, Yanming; Liu, Limin; Si, Yejun; Miao, Miao; Qiu, Huiying; Tang, Xiaowen; Han, Yue; Fu, Chengcheng; Jin, Zhengming; Chen, Suning; Sun, Aining; Wu, Depei
ABSTRACT: Objectives: To compare the outcomes of antihuman T lymphocyte globulin (ATG-F) and porcine antihuman lymphocyte globulin (p-ALG) as part of a conditioning regimen in hematopoietic stem cell transplantation (HSCT) for severe aplastic anemia (SAA). Methods: we performed a retrospective analysis, evaluating the outcome of patients with SAA who received ATG-F based conditioning ( n  = 26) with those receiving p-ALG conditioning ( n  = 34). Results: The median time to neutrophil engraftment was 11 days (range, 8 − 38) and 11 days (range, 9 − 24) in the p-ALG and ATG-F groups ( P  = 0.857); the median platelet engraftment time was 15 (range, 9 − 330) days and 13 (range, 10 − 56) days ( P  = 0.155). There were no significant differences in grades II − IV acute graft-versus-host disease (aGVHD), grades III − IV aGVHD, chronic GVHD (cGVHD), and the moderate-severe cGVHD between the ATG-F and p-ALG groups ( P >0.05). Discussion: Patients in the ATG-F group functioned significantly better on role-physical ( P  = 0.006), general health ( P  = 0.029), and physical component summary ( P  = 0.009). The estimated overall survival and failure free survival rates at 5 years were 88.5% ± 6.3% vs. 82.4% ± 6.5% ( P  = 0.515), 84.6% ± 7.1% vs. 79.4% ± 6.9%, respectively ( P  = 0.579). The infection rates were 61.53% and 47.05%, respectively ( P  = 0.265). Conclusion: As part of the conditioning regimen, p-ALG achieved a similar efficacy as ATG-F without increasing the incidence of transplantation complications in SAA patients.